Infinitival complements in a corpus of Classical Portuguese - Magalhães, Miguel (2016)
This paper aims to contribute to a better understanding of inflected infinitve in Classic Portuguese. In works such as Martins (2006) and Fiéis & Madeira (2014) we have observed that the distribution of inflected infinitives changed from Old to Modern Portuguese. Based on a corpus from an archive located in Braga district, with notarial texts from the XVII century (1650-1700), we will describe the use of inflected infinitives in infinitival complementation in this period, showing the conditions that allowed its widening to other contexts in Modern Portuguese.